Національна історія у проектах позитивістської адаптації та модерністської актуалізації: Л. Старицька-Черняхівська - Леся Українка - Романов, Сергій; Romanov, Serhiі (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуто дві різні моделі освоєння історичного матеріалу, представлені історіософськими концепціями і творчими практиками Лесі Укра- їнки та Л. Старицької-Черняхівської. У першому випадку рецептивний потен- ціал твору визначається сприйняттям авторкою безмежного дисперсного поля, яким є історія. Фантазії «на тему», як і сумлінна белетризація підручника, були для неї однаково неприйнятними способами освоєння минулого. За «вільгот- ністю» першого та дріб’язковою ретельністю другого губилося основне, за чим варто шукати письменника, – сутність, живий нерв, свідомість давніх епох. До таких лоцій найкраще надавався інтуїтивно-образний, а не реалістично-понятій- ний підхід, який апробувала Л. Старицька-Черняхівська. In this article the two different models of mastering of the historical document over history-philosophy conceptions and creative works of Lesіa Ukrainka and L. Sta- rytska-Cherniakhivska are outlined. In the first occasion the receptive potential of writing defines by author’s perception of the limitless dissimilar space of a history. The free fantasies and the diligent paraphrase of textbook wasn’t to her by good method of recognition history. A freestyle the first and a trifling the second method haven’t the main of writer’s need – essence, alive nerve, consciously of the past epochs. For that purpose is intuitive and figurative but isn’t realistic and conception approach, that L. Starytska-Cherniakhivska used by. That approach definitely use in state-positive restore of collective past, when colonic (without rights and perspec- tives) nation aspires to confirm its presence into the world culture and political space. That way appealed, almost fully, to the national traditions and restored and widen its to “inward use”.
National History Over the Projects Positivistic Adaptation and Modern Actualization: Lesіa Ukrainka – L. Starytska-Chernіakhivska
Keywords: розповідь; історія; міф; концепція; мистецтво; колонія; імперія; правда; narration; history; myth; conception; art; colony; imperia; truth